EVALUATION OF ENDOSCOPIC AND HISTOPATHOLOGIC RESULTS OF GASTRIC CANCERS - L. DEMİRTÜRK; S. HÜLAGÜ; M. YAYLACI; E. UÇMAKLI; M. ALTIN; L. DUMANHAN; A. VARDAR; A. ALTAŞ; M. DANACI (Turkish Journal of Gastroenterology, 2020)
-